FABRICS IN PALEMBANG COMMUNITY LIFE - FARIDA FARIDA; ROSMAIDA SINAGA (Sriwijaya University Learning and Education International Conference, 2016)
The purpose of this paper is to describe the role of the fabric community inPalembang from time to time. Fabric is a vital necessity that can not be separatedfrom daily life of Palembang community. At the beginning, this vital need only bemet by using wood as a raw material. On the development, the processing of woodfiber materials was growing. In addition the use of cotton fabrics from India andChina silk is also increasingly becoming an integral part in the life of thearchipelago. Palembang occupied a special position in the cloth trade, especially asmost potential fabric lovers in Southeast Asia, together with Jambi. Both of theregions known as the Southeast Sumatra. The function of fabric for Palembangsociety is very diverse, ranging from meeting the needs of body armor consisting offabric, and scarves, to other functions. These functions among others, as a symbol ofone's status, prizes, a medium of exchange, pay fines, media peace, a symbol of thebond, the means of diplomacy, prestige and heritage, thus, the position ofPalembang as a connoisseur and developer of cloth until now continues. So normalthat until now Palembang is famous as the sole producer of the most beautiful fabricknown as the Queen of fabric which is Songket Fabric.